On the Reducibility of a Class of Linear Almost Periodic Differential Equations (Communications in Mathematical Research, 2020)
In this paper, we use KAM methods to prove that there are positive measure Cantor sets such that for small perturbation parameters in these Cantor sets a class of almost periodic linear differential equations are reducible.